2010
DOI: 10.1042/bc20090145
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and cellular functions of the ESCRT machinery in pluricellular organisms

Abstract: ESCRTs (endosomal sorting complexes required for transport) were first discovered in yeast and are known to be required in the biogenesis of the MVB (multivesicular body). Most ESCRT research has been carried out in vitro using models such as yeast and mammalian cells in culture. The role of the ESCRTs genes in endosome maturation is conserved from yeast to mammals, but little is known about their function during development in multicellular organisms. Since ESCRTs play a leading role in regulating some cell s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 90 publications
0
39
1
Order By: Relevance
“…Redundant transmembrane receptors are sorted to intraluminal vesicles predestined for lysosomal degradation after ubiquitination, a post-translational modification that is executed by ESCRT (Babst, 2005;Michelet et al, 2010). On the other hand, there is no compelling evidence that the ESCRT is involved in the sorting of transmembrane receptors to intraluminal vesicles that are predestined to become secreted as exosomes Buschow et al, 2005Buschow et al, , 2009Trajkovic et al, 2008;Simons and Raposo, 2009;Tamai et al, 2010;Bobrie et al, 2011).…”
Section: A Exosomesmentioning
confidence: 97%
“…Redundant transmembrane receptors are sorted to intraluminal vesicles predestined for lysosomal degradation after ubiquitination, a post-translational modification that is executed by ESCRT (Babst, 2005;Michelet et al, 2010). On the other hand, there is no compelling evidence that the ESCRT is involved in the sorting of transmembrane receptors to intraluminal vesicles that are predestined to become secreted as exosomes Buschow et al, 2005Buschow et al, , 2009Trajkovic et al, 2008;Simons and Raposo, 2009;Tamai et al, 2010;Bobrie et al, 2011).…”
Section: A Exosomesmentioning
confidence: 97%
“…Ultimately, ILVs are degraded after fusion with the lysosome (Gruenberg and Stenmark, 2004;Piper and Katzmann, 2007). Recent studies in the nematode, fly and mammals have shown that mutations in the endosomal sorting complexes required for transport (ESCRT) block endosomal maturation but also lead to an increased number of autophagosomes (Michelet et al, 2009;Michelet et al, 2010;Roudier et al, 2005;Rusten et al, 2007a;Rusten and Stenmark, 2009). The ESCRT machinery is composed of four complexes, ESCRT-0 to ESCRT-III, which are essential for the formation of ILVs in the MVB compartment and for the sorting of ubiquitylated membrane proteins.…”
Section: Introductionmentioning
confidence: 99%
“…However, this complex regulation of Arabidopsis ESCRT is perhaps not surprising given a number of factors, including: (1) the considerable expansion of many of the ESCRT gene families in plants compared with other eukaryotes, 4,5,15 (2) the sophisticated hierarchical-and stoichiometric-dependent manner in which the various multi-protein ESCRT subcomplexes, their associated regulatory proteins, as well as ubiquitin, appear to operate in concert, [1][2][3]36 (3) the unique and dynamic nature of the plant endosomal pathway overall, 17,18,37 and (4) the ever expanding number of roles that the ESCRT machinery, or at least portions thereof, participates in throughout plant growth and development. 8 Undoubtedly these and other important aspects of the plant ESCRT machinery will be the focus over the coming years of more detailed experimental studies and the results presented here should thus serve as a useful resource for elucidating the molecular mechanisms by which ESCRT functions in plants. …”
mentioning
confidence: 99%